2014
DOI: 10.17014/ijog.v1i2.180
|View full text |Cite
|
Sign up to set email alerts
|

Epithermal Gold-Silver Deposits in Western Java, Indonesia: Gold-Silver Selenide-Telluride Mineralization

Abstract: -The gold-silver ores of western Java reflect a major metallogenic event during the Miocene-Pliocene and Pliocene ages. Mineralogically, the deposits can be divided into two types i.e. Se-and Te-type deposits with some different characteristic features. The objective of the present research is to summarize the mineralogical and geochemical characteristics of Se-and Te-type epithermal mineralization in western Java. Ore and alteration mineral assemblage, fluid inclusions, and radiogenic isotope studies were und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Bortnikov et al (1987) showed that the development of Se-bearing minerals in ore is evidence for the high oxidation potential of the ore-formation medium, which may result from mixing of ore-bearing fluids with highly aerated meteoric water. The widespread selenium mineralization in ore testifies to near-surface ore deposition and insignificant erosion (Kovalenker, 2007;Yuningsih et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bortnikov et al (1987) showed that the development of Se-bearing minerals in ore is evidence for the high oxidation potential of the ore-formation medium, which may result from mixing of ore-bearing fluids with highly aerated meteoric water. The widespread selenium mineralization in ore testifies to near-surface ore deposition and insignificant erosion (Kovalenker, 2007;Yuningsih et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A selenium impurity (up to 1.86 wt %) has been detected in electrum (Table 2). It should be noted that enrichment of main ore minerals in selenium is a typomorphical feature of high-grade ore of epithermal low-sulfidation deposits Yuningsih et al, 2014).…”
Section: Geological Structure and Ore Composition Of The Depositmentioning
confidence: 99%
“…A previous study mentioned that the abundance of mineral deposit in this area is mostly controlled by advanced magma evolution that increases the alkali content of the magmatichydrothermal system (Setijadji et al, 2006). The mineralization is interpreted to have occurred during the Mio-Pliocene period based on K-Ar dating from surrounding areas (McInnes et al, 2004;Yuningsih et al, 2014). Syn-ore structures are likely the result of subduction activity in southern Java as indicated by the lineament pattern, while the pre-ore structures are associated with caldera formation in the Bayah Dome Volcanic Complex as suggested by the presence of a regional circular (caldera-like) structure.…”
Section: Genetic Modelmentioning
confidence: 99%
“…С другой стороны, островная дуга Сунда-Банда, как и другие вулканические провинции, связанные с зонами субдукции, является областью локализации экономически значимых медно-порфировых и эпитермальных Au-Ag месторождений [12][13][14][15][16]. Известно, что эволюция большинства мантийных и коровых силикатных магм неизбежно приводит к несмесимости силикатного и несиликатного расплавов [17].…”
unclassified